Kwalifikacja przychodów nierezydentów z tytułu płatności za oprogramowanie i świadczenie usług Cloud Computingu - Wirski, Jakub (Kwartalnik Prawa Podatkowego, 2015)
The aim of this article is to analyse the characterisation of income typical for the digital economy, derived by non-residents. The article refers to the payments for software from both perspectives – the Polish tax law and the international tax law. The following sorts of payments were analysed in this respect: for the use of a copyright on software (including payments for so-called end-user licences), for the sale of a copyright on software and for the sale of a copy of software in case of an exhaustion of a copyright in this area. The article encompasses also analysis of the characterisation of payments for Cloud Computing services from both perspectives – the Polish tax law and the international tax law, especially provisions of law related to the following payments: for the use of a copyright, for data processing services, for the use of technical equipment and for technical services.